2004
DOI: 10.1093/jnci/djh185
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Foods, Calcium, and Colorectal Cancer: A Pooled Analysis of 10 Cohort Studies

Abstract: Higher consumption of milk and calcium is associated with a lower risk of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
327
2
18

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(374 citation statements)
references
References 54 publications
27
327
2
18
Order By: Relevance
“…22,54 Data from both a pooled analysis of CRC cohort studies and a randomized trial of calcium supplementation for CRA recurrence prevention indicate that the protective effects of high calcium intake are seen only in individuals who also have a high intake or high circulating levels of vitamin D. 22,53 Conversely, the benefits of high vitamin D levels are restricted to individuals with high calcium intake. In the United States, dairy products are an important source of both calcium and vitamin D, and may therefore exert a greater influence than micronutrient considered in isolation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,54 Data from both a pooled analysis of CRC cohort studies and a randomized trial of calcium supplementation for CRA recurrence prevention indicate that the protective effects of high calcium intake are seen only in individuals who also have a high intake or high circulating levels of vitamin D. 22,53 Conversely, the benefits of high vitamin D levels are restricted to individuals with high calcium intake. In the United States, dairy products are an important source of both calcium and vitamin D, and may therefore exert a greater influence than micronutrient considered in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium in milk is highly bioavailable, which may make milk appear to be associated with CRC risk independent of total calcium intake. 53 Alternatively, the protective effects of dairy products may be due to other components, such as conjugated linoleic acid and lactoferrin, which inhibit colonic carcinogenesis in animal models, 55,56 or the milk protein casein, which has been reported to have antimutagenic activity on the digestive tract. 57 Randomized trials of calcium supplementation indicate a modest but significant protective effect against CRA recurrence (pooled RR from 3 trials combined 0.80, 95%CI: 0.68-0.93).…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of fermented milk products is reported to have many benefits to human health around the world [1][2][3][4][5][6] . Yoghurt is the most known fermented dairy product with high consumption worldwide mainly because of the many health-promoting effects [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] In addition to a meta-analysis of observational studies supporting the relation of vitamin D and lower colorectal cancer risk, 8 a recent meta-analysis of randomized trials indicates vitamin D supplementation likely decreases risk of all-cause mortality, with benefits for cancer thought to be a major explanatory factor. 9 Consistent with a 5 year vitamin D trial that suggested benefits against colorectal cancer mortality, 10 a large randomized trial indeed demonstrated that moderate dose 1,000 IU vitamin D and calcium supplementation substantially reduces all-cancer risk after 1-4 years follow-up RR 5 0.23 (95% CI: 0.09-0.60), 11 where vitamin D significantly contributed benefit beyond calcium supplementation alone.Similarly, however, calcium may also impede colonic carcinogenesis via a variety of mechanisms, 3 as calcium has been inversely associated with colorectal cancer risk in prospective studies, 12,13 and also been demonstrated to be protective against colorectal carcinogenesis and adenomas in multiple randomized trials. [14][15][16][17] Furthermore, a large pooled analysis of 10 international prospective cohorts found that milk and calcium intakes were both associated with significantly lower risk of colorectal cancer, with the relative risks, comparing highest vs. lowest categories of intake, of 0.85 (95% CI: 0.78, 0.94) for milk and 0.78 (95% CI: 0.69, 0.88) for calcium.…”
mentioning
confidence: 99%